PENGARUH PENAMBAHAN SERBUK SENG (ZNO POWDER) TERHADAP BERAT, KUAT TEKAN DAN KUAT TARIK BELAH BETON - Maulana Ibrahim; Eka Juliafad (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
Indonesia is a developing country that has quite advanced industrial prospects, one of which is the zinc industry. Increased zinc production, will also increase zinc waste. Based on the nature of ZnO which readily reacts with other compounds, this compound can be used as a mixture in making concrete so that it can produce quite good structural strength. This study aims to determine how the effect of using zinc powder on weight, compressive strength and split tensile strength of concrete. The variations in the addition of zinc powder consisted of 0.25%, 0.5%, 0.75% and 1% by weight of the cement used. The test object used is a cylinder with a size of 15 cm x 30 cm. Tests for weight, compressive strength and split tensile strength were carried out when the concrete was 28 days old. The results obtained are for the weight of concrete with variations in the addition of zinc powder as much as 0%, 0.25%, 0.75% and 1% respectively of 2294 Kg / m3, 2305 Kg / m3, 2311 Kg / m3, 2305 Kg / m3, 2323 Kg / m3. Meanwhile, the compressive strength is 30.49 MPa, 30.356 MPa, 32.92 MPa, 32.69 MPa and 31.573 MPa. And for the tensile strength of concrete with the same variations, namely 11.306 MPa, 10.597 MPa, 11.976 MPa, 13.07 MPa and 13.426 MPa.